Farmer perceptions of cassava bacterial blight disease in Oyo State , southwest, Nigeria - Chukwuka, K.; Okechukwu, R.U.; Azorji, J. (2013)
The study was specifically undertaken to appraise farmers' perception to cassava bacterial blight disease that ravages cassava in most cassava growing regions of sub-Saharan Africa and Asia. The study revealed that majority of the cassava farmers in the sampled area were averagely young, experienced in farming cassava with a fairly good level of education. The study revealed that majority of farmers are not aware that the disease exists in their farms, in most cases it is considered same as senescence of leaves. Most of them have not participated in training addressing cassava diseases. This underscores the need to enlighten farmers on cassava diseases that lead to yield losses, and the need to fully adopt improved genotypes. Adoption of other disease management strategies such as farm sanitation, use of high quality planting materials from known sources need to be regularly communicated to farmers by organizing training programs, workshops, and field days as this would aid reduce severity of disease in farmers' field and thus improve food security.